2013
DOI: 10.5005/jp-journals-10084-12124
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Hand Massage vs Foot Massage for Pain in Incision Site among Post-cesarean Mothers Admitted in Obstetrical Care Units at Mahatma Gandhi Medical College and Research Institute, Puducherry

Abstract: Background: Cesarean section is the most frequently performed surgery worldwide. Massage is one of the cheapest and cost-effective methods to reduce pain among post-cesarean mothers. Materials and methods: In this study, a true experimental research design was used. The population of the study was post-cesarean mothers during first postoperative day. A sample of 90 post-cesarean mothers was selected by using a simple random sampling technique, with 30 mothers in each group: group I received hand massage, group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Similar results were found in a previous study that showed a significant difference in the pain score in the experimental and control groups. 11 There is no association between preintervention pain score and selected baseline variables. The study found that there was no association between pain level and age (χ 2 ¼ 1.45), education (χ 2 ¼ 3.23), and previous history of LSCS (χ 2 ¼ 1.84).…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were found in a previous study that showed a significant difference in the pain score in the experimental and control groups. 11 There is no association between preintervention pain score and selected baseline variables. The study found that there was no association between pain level and age (χ 2 ¼ 1.45), education (χ 2 ¼ 3.23), and previous history of LSCS (χ 2 ¼ 1.84).…”
Section: Discussionmentioning
confidence: 98%
“…For centuries, massage therapy has used to treat pain. When it combined with drug therapy has found to help manage acute postoperative pain (13) . It involves manipulating soft tissues by hand to have a beneficial effect on how various body systems works.…”
Section: Introductionmentioning
confidence: 99%